The Impact of China's New Securities Law on Audit Quality and Fees: Moderating Effect of Internal Control and Media Coverage - Lu, Zhang (Universiti Malaysia Sarawak, 2025)
The China’s new Securities Law implemented in 2020 lowered the entry barriers for audit firms in the securities market, thereby intensifying competition within the audit sector. It also introduced a series of policy measures that further strengthened the regulation of listed companies and auditors, as well as increased the severity of penalties for violations. This study aims to investigate the impact of the new Securities Law on changes in audit quality and audit fees. Additionally, the study explores the moderating roles of internal control as an internal supervisory mechanism and media coverage as an external supervisory mechanism. Based on data from Chinese listed companies from 2016 to 2022, the study employs a Difference-in-Differences (DiD) approach to empirically test the hypotheses. The findings reveal that the implementation of the new Securities Law has significantly improved the audit quality of listed companies, with the effect being particularly pronounced in firms with weaker internal controls. Moreover, extensive media coverage further amplifies the positive impact of the law on audit quality. Simultaneously, the study observes a significant increase in audit fees following the implementation of the law, reflecting the heightened compliance requirements and stricter regulatory scrutiny that influence auditors' pricing decisions. This increase in audit fees is less pronounced in companies with stronger internal controls, indicating that robust internal controls can mitigate some of the cost pressures associated with the new regulations. These results are consistent with the predictions of audit risk theory and reputation theory. The study employs rigorous robustness tests, including parallel trends test, placebo tests, and Propensity Score Matching Difference-in-Differences (PSM-DiD) analyses, to confirm the reliability of the findings. The study provides important insights into how the China’s new Securities Law impacts audit quality and audit fees. Overall, while the revised Securities Law has successfully enhanced market transparency and audit quality, it has also increased compliance costs for companies with lower governance standards. These findings carry significant theoretical and practical implications for policymakers, regulators, and market participants in China and other emerging economies.